"The roots" of selenium toxicity: A new concept. (2nd October 2016) - Kolbert, Zsuzsanna; Lehotai, Nóra; Molnár, Árpád; Feigl, Gábor
ABSTRACT: Elevated levels of selenium (Se) cause toxicity in non-accumulator plant species. The primary reasons for toxic Se effect have been considered to be selenoprotein accumulation and oxidative stress. However, based on our recent paper in Plant Cell Reports and previous literature data we suggest that disturbances in the homeostasis of both reactive oxygen and nitrogen species result in selenium-induced nitro-oxidative stress, contributing to toxicity. The most characteristic symptom of Se exposure is the inhibited root elongation which is partly caused by hormonal disturbances. Our recent paper suggests the involvement of cytokinin in selenium stress sensing of the root systemAltogether, the aim of this Addendum is to present reactive nitrogen species and phytohormones as new players in plant selenium toxicity.